Oral Contraceptive Use at the Time of ACL Reconstruction Decreases Risk of Revision Surgery - Sujay Garlapati; Rajit Agarwal; Meghan Bishop (Sports Health: A Multidisciplinary Approach, 2026)
Background: Anterior cruciate ligament (ACL) reconstruction is associated with a significant risk of revision surgery. Oral contraceptive pills (OCPs) suppress endogenous estrogen and progesterone levels and have been associated with reducing the risk of primary ACL injuries in women. Hypothesis: OCP use at the time of initial ACL reconstruction is associated with a reduced risk of subsequent ipsilateral procedures in female patients and an elevated risk of venous thromboembolism (VTE). Study Design: Cohort study. Level of Evidence: Level 3. Methods: A retrospective cohort study was conducted using the TriNetX database to compare female patients aged 13 to 49 years with and without documented OCP use at the time of initial ACL reconstruction. Cohorts were further stratified by time from reconstruction, age, body mass index, and diabetes status. Risk ratios with 95% CIs were calculated to evaluate the risk of subsequent ipsilateral procedures and VTE. Results: Out of 26,520 patients who underwent ACL reconstruction, 1736 (6.5%) underwent subsequent ipsilateral ACL reconstruction within 5 years. Documented OCP users at the time of initial ACL reconstruction had a 25.0% lower risk of subsequent ipsilateral ACL reconstruction surgery within 5 years compared with nonusers (risk ratio [RR] = 0.750; P < 0.01). The protective effect was strongest in the first year (RR = 0.420; P < 0.01) and remained significant at 2 (RR = 0.471; P < 0.01), 3 (RR = 0.612; P < 0.01), and 4 years (RR = 0.600; P = 0.01). For loss-of-motion procedures, OCP use was associated with a 73% decreased risk within 1 year (RR = 0.269; P < 0.01). OCP use did not increase VTE risk significantly within 5 years (RR = 1.30; P = 0.10). Conclusion: OCP use at the time of initial ACL reconstruction in female patients was associated with a reduced risk of subsequent ipsilateral procedures, without increasing VTE risk. Clinical Relevance: These findings highlight the potential of OCPs to reduce the physical and economic burden of revision in high-risk populations.